2010
DOI: 10.1158/0008-5472.can-10-2074
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-183 Functions as an Oncogene by Targeting the Transcription FactorEGR1and Promoting Tumor Cell Migration

Abstract: The transcription factor EGR1 is a tumor suppressor gene that is downregulated in many cancer types. Clinically, loss of EGR1 translates to increased tumor transformation and subsequent patient morbidity and mortality. In synovial sarcoma, the SS18-SSX fusion protein represses EGR1 expression through a direct association with the EGR1 promoter. However, the mechanism through which EGR1 becomes downregulated in other tumor types is unclear. Here, we report that EGR1 is regulated by microRNA (miR)-183 in multipl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
213
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 259 publications
(230 citation statements)
references
References 43 publications
9
213
1
6
Order By: Relevance
“…However, the effects of their coordinate expression on the mechanisms of tumorigenesis and particularly the proliferation of colon cancer remain to be fully elucidated. In the present study, this cluster was overexpressed in colon cancer, which was in accordance with a previous study (21). A series of transfection oligo-nucleotides were designed to detect the effects of the miR-183/96/182 cluster in colon cancer.…”
Section: Simultaneous Knockdown Of the Expression Of The Mir-183/96/1supporting
confidence: 86%
See 1 more Smart Citation
“…However, the effects of their coordinate expression on the mechanisms of tumorigenesis and particularly the proliferation of colon cancer remain to be fully elucidated. In the present study, this cluster was overexpressed in colon cancer, which was in accordance with a previous study (21). A series of transfection oligo-nucleotides were designed to detect the effects of the miR-183/96/182 cluster in colon cancer.…”
Section: Simultaneous Knockdown Of the Expression Of The Mir-183/96/1supporting
confidence: 86%
“…It has been demonstrated that miR-183, 96 and 182 act as tumor oncogenes based on their high expression levels in colon cancer tissues (21). Therefore, the present study used ASO-miRs to knockdown the expression of the miR-183/96/182 cluster.…”
Section: Simultaneous Knockdown Of the Expression Of The Mir-183/96/1mentioning
confidence: 94%
“…miR-183-5p was reported to be an early predictive biomarker for prostate cancer with aggressive progression characteristics (Larne et al, 2013), while conversely in lung cancer its expression was decreased . The tumor suppressor PTEN (phosphatase and tensin homolog deleted on chromosome ten) is known to be regulated by miR-183-5p (Sarver et al, 2010). While no previous findings have characterized miR-183-5p in NPC, our data revealed a significant the correlation between miR-183-5p and the NPC N stages (p<0.05).…”
Section: Discussionsupporting
confidence: 39%
“…Previously, our group already reported on a larger study that included gene and miRNA network analysis of osteosarcoma, MPNST, neurofibroma, and rhabdomyosarcoma. [11][12][13] For functional analysis, upstream regulator analysis, and miRNA targeting analysis, we used Ingenuity Pathway Analysis (IPA) software (Qiagen, Redwood City, CA, USA). IPA uses a right-tailed Fisher's exact test to calculate a P-value corresponding to the probability that a biologic function not relevant to the input data set is falsely identified as relevant.…”
Section: Data Analysesmentioning
confidence: 99%